Peroxisomal regulation of energy homeostasis: Effect on obesity and related metabolic disorders - Brian Kleiboeker; Irfan J. Lodhi (Molecular Metabolism, 2022)
Background: Peroxisomes are single membrane-bound organelles named for their role in hydrogen peroxide production and catabolism. However, their cellular functions extend well beyond reactive oxygen species (ROS) metabolism and include fatty acid oxidation of unique substrates that cannot be catabolized in mitochondria, and synthesis of ether lipids and bile acids. Metabolic functions of peroxisomes involve crosstalk with other organelles, including mitochondria, endoplasmic reticulum, lipid droplets and lysosomes. Emerging studies suggest that peroxisomes are important regulators of energy homeostasis and that disruption of peroxisomal functions influences the risk for obesity and the associated metabolic disorders, including type 2 diabetes and hepatic steatosis. Scope of review: Here, we focus on the role of peroxisomes in ether lipid synthesis, β-oxidation and ROS metabolism, given that these functions have been most widely studied and have physiologically relevant implications in systemic metabolism and obesity. Efforts are made to mechanistically link these cellular and systemic processes. Major conclusions: Circulating plasmalogens, a form of ether lipids, have been identified as inversely correlated biomarkers of obesity. Ether lipids influence metabolic homeostasis through multiple mechanisms, including regulation of mitochondrial morphology and respiration affecting brown fat-mediated thermogenesis, and through regulation of adipose tissue development. Peroxisomal β-oxidation also affects metabolic homeostasis through generation of signaling molecules, such as acetyl-CoA and ROS that inhibit hydrolysis of stored lipids, contributing to development of hepatic steatosis. Oxidative stress resulting from increased peroxisomal β-oxidation-generated ROS in the context of obesity mediates β-cell lipotoxicity. A better understanding of the roles peroxisomes play in regulating and responding to obesity and its complications will provide new opportunities for their treatment.